PENDAMPINGAN POSYANDU REMAJA SEBAGAI UPAYA HUKUM PREVENTIF PENCEGAHAN KENAKALAN REMAJA DI DESA BANARAN KECAMATAN GEGER KABUPATEN MADIUN - Retno Catur Kusuma Dewi; Agus Wiyaka; Retno Iswati (Universitas Merdeka Madiun, 2025)
The transition period from childhood to adulthood often causes adolescents to experience problems. This period occurs between the ages of 10 and 19 and is not yet married. The Perdoski report states that the number of sexually transmitted diseases (STDs) in adolescents in Indonesia continues to increase from 2017. Adolescent exposure to STDs can be triggered by juvenile delinquency such as premarital sexual intercourse, drugs, free sex which of course has an impact on extramarital pregnancy, school dropouts, early marriage, abortion, risky childbirth, sexually transmitted diseases. The effort to anticipate juvenile delinquency is through the establishment of Posyandu Remaja. Posyandu Remaja is part of the ARU (Children, Adolescents and Elderly) Programme, as a flagship programme of the Ministry of Health and is implemented in the Madiun District Health Office. This programme promotes a preventive approach because it is centred on primary health care activities in a holistic manner. The implementation of this program is the result of collaboration between lecturers and students of Universitas Merdeka Madiun Real Work Lecture with UPTD Puskesmas Geger District, Madiun Regency in a community service program which aims to provide socialisation of adolescent posyandu through health education on how to address problems during puberty. This activity was attended by young people in Banaran Village, Geger District, Madiun Regency, health education activities were provided through the lecture method and at the end of the activity an evaluation of adolescent knowledge was carried out. The results of community service activities show that adolescents have increased knowledge about how to respond to problems at puberty. Similar coaching activities can be used as a preventive measure carried out on an ongoing basis and can be developed towards regular health screening, especially STDs in adolescents.